Pola Resistensi Antibiotik Pada Pasien Dewasa yang Menderita Pneumonia di RS Usu Periode Januari 2017 – Desember 2018 - Fathin, Aditasari; Kusumawati, Lia (CV RIFAINSTITUT, 2022)
Pneumonia is defined as an acute lower respiratory tract infection in the lung parenchyma caused by microorganisms such as bacteria, viruses, fungi, and parasites. This study was conducted to see the pattern of bacterial resistance to antibiotics in patients with pneumonia. This research is descriptive with a cross-sectional study approach. The study sample was adult patients diagnosed with pneumonia through culture and antibiotic sensitivity tests from blood or sputum samples. The sampling method used is total sampling. The data used is secondary data obtained through medical records. From 50 samples found 8 types of gram-positive bacteria with the highest percentage being Streptococcus alpha hemolytic (9.7%) and 12 gram-negative bacteria with the highest percentage being Klebsiella pneumoniae (21%). Antibiotics that are still sensitive to gram-positive bacteria with a percentage > 80% are chloramphenicol, erythromycin, imipenem, clarithromycin, metronidazole, netilmicin, nitrofurantoin, piperacillin, piperacillin-tazobactam, fosmicin, vancomycin, while antibiotics that are sensitive to Bacteria-negative antibiotics are azithromycin, clarithromycin, metronidazole, netilmicin, tigecycline, ertapenem and amikacin. The most common bacteria causing pneumonia at USU Hospital were gram-negative bacteria with the highest percentage being Klebsiella pneumoniae followed by Acinetobacter baumannii, Pseudomonas aeruginosa and Streptococcus alpha hemolytic